Sosialisasi Perilaku Bullying di Kalangan Siswa MTs Al-Manar Medan - Dani Muliadi; M, Faisal Husna; Loni Rut Seripani; Meysa Dwi Anggini; Febri Maharani; Nazwa Revalina Sabylla; Ahmad Zizou; Anissa Salsabina Lesti; Sakina (Pencerah, 2025)
The aim of socialization regarding bullying behavior is to increase students' awareness of bullying, teach them how to deal with bullying behavior, encourage a sense of empathy, build self-confidence, improve relationships between students, and prevent bullying behavior. Our implementation method is through lectures and questions and answers. In this lecture and question and answer method, we provide education regarding the dangers of bullying behavior among MTS AL-MANAR Medan students. The results of the socialization carried out at MTS Al-Manar Medan regarding bullying behavior are as follows: Increased student insight regarding the impact and behavior of bullying, awareness among students to prevent bullying behavior, increased self-confidence to fight bullying behavior. Socialization and education about bullying behavior succeeded in increasing students' insight regarding the dangers of bullying behavior in class 7A MTS Al-Manar Medan. However, there needs to be further action and cooperation from the school to ensure maximum results.